Hydrochloric acid‐enhanced radiofrequency ablation for treating a large hepatocellular carcinoma with spontaneous rapture: a case report. Issue 1 (7th January 2017) - Huang, Jin‐Hua; Morelli, John N.; Ai, Fei; Zou, Ru‐Hai; Gu, Yang‐Kui; Gao, Fei; Zhang, Tian‐Qi; Yao, Wang; Jiang, Xiong‐Ying; Zhang, Yan‐Yang
Abstract: Background: A ruptured hepatocellular carcinoma (HCC) is often fatal. In addition to surgery and transarterial embolization, radiofrequency ablation (RFA) might be another option for treating a ruptured HCC. Unfortunately, conventional RFA has a limited ablation zone; as such, it is rarely used to treat ruptured tumors. Case presentation: This case was a 60‐year‐old man who had a large, ruptured HCC in which hydrochloric acid (HCl)‐enhanced RFA successfully controlled the bleeding and made the tumor completely necrotic. Conclusion: Considering the effectiveness of HCl‐enhanced RFA in achieving hemostasis and tumor ablation, it might be a new option for treating large, ruptured HCCs.